2022
DOI: 10.16899/jcm.1033147
|View full text |Cite
|
Sign up to set email alerts
|

The Attitudes of Undergraduate Nursing Students to Childhood Vaccines

Abstract: This study aims to determine the attitudes of undergraduate nursing students studying at a public university toward childhood vaccines and investigate whether students' attitudes change according to sociodemographic characteristics, vaccination history, and perceived level of knowledge. Material and Method:This descriptive study was conducted with 83 students studying in the Department of Nursing at a public university in Konya between May 2020 and September 2021. The data were collected using the Information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In studies conducted in Turkey and worldwide, different determinations were made about vaccination attitudes according to gender. A study conducted in 2022 with nursing students in Turkey showed that males had a more negative vaccine attitude [ 25 ]. In a study conducted in 2022 in Turkey, no difference was observed in vaccination attitudes according to gender [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted in Turkey and worldwide, different determinations were made about vaccination attitudes according to gender. A study conducted in 2022 with nursing students in Turkey showed that males had a more negative vaccine attitude [ 25 ]. In a study conducted in 2022 in Turkey, no difference was observed in vaccination attitudes according to gender [ 24 ].…”
Section: Discussionmentioning
confidence: 99%